To determine the validity of the equation \((3\sqrt{4})^{24}/(\sqrt{3})^{6}=(4/3)^{5}\), let's simplify both sides step by step.
Left Side: \[ \frac{(3\sqrt{4})^{24}}{(\sqrt{3})^{6}} \]
-
Simplify \( \sqrt{4} \): \[ \sqrt{4} = 2 \] So \( (3\sqrt{4})^{24} = (3 \cdot 2)^{24} = (6)^{24} \).
-
Now for the denominator: \[ (\sqrt{3})^{6} = (3^{1/2})^{6} = 3^{6/2} = 3^{3} = 27 \]
-
Now, rewrite the left side: \[ \frac{(6)^{24}}{27} = \frac{6^{24}}{3^{3}} = 6^{24} \cdot 3^{-3} \]
Right Side: \[ \left(\frac{4}{3}\right)^{5} = \frac{4^5}{3^5} \]
Comparison: To simplify further we can express \(6^{24}\): \[ 6^{24} = (2 \cdot 3)^{24} = 2^{24} \cdot 3^{24} \] Then substituting that in: \[ 6^{24} \cdot 3^{-3} = 2^{24} \cdot 3^{21} \]
Now let's simplify the right side: \[ \frac{4^5}{3^5} = \frac{(2^2)^5}{3^5} = \frac{2^{10}}{3^5} \]
Final Comparison: \[ 2^{24} \cdot 3^{21} \text{ (left side) } \quad \text{and } \quad \frac{2^{10}}{3^5} = 2^{10} \cdot 3^{-5} \text{ (right side)} \]
The powers of 2 and 3 on both sides are thus:
- Left side: \(2^{24}\) and \(3^{21}\)
- Right side: \(2^{10}\) and \(3^{-5}\).
Since these powers do not match, we can conclude:
The equation is False. The Power of a Power Property has not been applied correctly.
Thus, the correct response is: False. The Power of a Power Property has not been applied correctly.